Dissemination Of Public Information Through Online Media: Study on the Vision and Mission of the Mayor of Palu Hadianto Rasyid - Citra Antasari; A. Reza Fadillah Putri (IHSA Institute, 2022)
The service and management of public communication within the scope of government is one of the important principles that must be implemented by the Regional Government. Based on the Law-No. 14 of 2008 related to public information, the dissemination to the Palu City Government was carried out by the IKP (public communication information) which is a sub-section of the Palu City Communications and Information Office, as well as the involvement of the Palu City media center where both of them act as government officials. This research method is descriptive qualitative with a case study approach, and the use of data collection techniques of observation, documentation and in-depth interviews using purposive sampling technique. The dissemination was carried out through 4 online media platforms, namely websites, instagram, facebook and YouTube. Three of the four platforms use the name